2013
DOI: 10.1017/s0033291713001529
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and perinatal hypoxia associated with hippocampus/amygdala volume in bipolar disorder

Abstract: BackgroundPre- and perinatal adversities may increase the risk for schizophrenia and bipolar disorder. Hypoxia-related obstetric complications (OCs) are associated with brain anatomical abnormalities in schizophrenia, but their association with brain anatomy variation in bipolar disorder is unknown.MethodMagnetic resonance imaging brain scans, clinical examinations and data from the Medical Birth Registry of Norway were obtained for 219 adults, including 79 patients with a DSM-IV diagnosis of bipolar disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…These alterations may be generated during a perinatal neurodevelopmental period. During this period, severe obstetric complications and perinatal asphyxia have been reported to be related to smaller hippocampal volumes in patients with non-psychotic BD (Haukvik et al 2014), whereas patients with psychotic features were exposed to maternal serological influenza as a risk factor (Canetta et al 2014). CA1 receives input from CA2/3 and projects to the subiculum, where a higher number of neurons indicates the same pathophysiology as in CA1.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations may be generated during a perinatal neurodevelopmental period. During this period, severe obstetric complications and perinatal asphyxia have been reported to be related to smaller hippocampal volumes in patients with non-psychotic BD (Haukvik et al 2014), whereas patients with psychotic features were exposed to maternal serological influenza as a risk factor (Canetta et al 2014). CA1 receives input from CA2/3 and projects to the subiculum, where a higher number of neurons indicates the same pathophysiology as in CA1.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic differences in total hippocampal formation volumes were studied using the same model, with the hippocampal formation as the dependent variable. In concordance with previous studies by our group, we performed subgroup analyses on patients within the bipolar spectrum [psychotic vs. nonpsychotic bipolar disorder (41) and bipolar I vs. bipolar II disorder (2)]. …”
Section: Statistical Analysesmentioning
confidence: 97%
“…Similarly, a linear relationship between birth weight and the risk for BD as well as other psychiatric disorders was found (Abel et al, 2010), and children delivered by cesarean section had a 2.5-fold greater risk for BD in a large population-based register (Chudal et al, 2013). A recent study that reported an association between perinatal hypoxia and reduced left amygdala and right hippocampal volumes in psychotic and non-psychotic BD subjects, respectively, raises the possibility that perinatal complications increase the risk for developing BD by impacting key circuits involved in the regulation of emotion (Haukvik et al, 2013).…”
Section: Evidence For a Neurodevelopmental Etiologymentioning
confidence: 99%